A crypto-steganography scheme for IoT applications based on bit interchange and crypto-system - Suray Alsamaraee; Ali Salem Ali (Institute of Advanced Engineering and Science, 2022)
Image steganography and cryptography have been used widely due to the dramatic evolution of the internet of things (IoT) and the simplicity of capturing and transferring digital images. Pressing challenges in the context of a steganography system include security, imperceptibility, and capacity issues. In the existing schemes, fixing one issue has been indicated to affect the other and vice versa. Based on the above challenges, a new scheme has been proposed for the Crypt-steganography scheme. The proposed scheme consists of three main contributions. The first contribution is hybrid additive cryptography (HAC), which is related to encrypting secret messages before the embedding process to ensure security. The HAC depends on ElGamal elliptic curve cryptosystem (ECC) with cubic Bézier curve to achieve text confidentiality. The second contribution is a bit interchange method (BIGM), which is related to the embedding process and solves the image's imperceptibility. The third contribution is a new image partitioning method (IPM). The IPM contribution increases the randomization of selecting the embedding pixels. The IPM proposes a random pixel selection based on three iterations of the Hénon Map function used with IPM. Different parameters are used to evaluate the proposed scheme. Based on the findings, the proposed scheme gives evidence to overcome existing challenges.